Effect on thrust due to damaged propellers of quadcopters - Aslin Haziqah Anuar (2019)
Quadcopters which are a type of Unmanned Aerial Vehicles (UAVs) are attracting a lot of attention for both commercial and personal usage. One of the many applications of UAVs is surveillance as it helps military personnel to reduce potential risks on one’s safety. As UAVs become more popular, it’s affordability of it increases with technology to manufacture these devices become more advance. However, these quadcopters may be damaged during operation and it is necessary to have flight stability even when one of the propeller is damaged. For example, during a military surveillance operation, quadcopters that are used need to maintain their control stability so that they would not jeopardize the safety of the armed forces. The main objective of this project is to analyse the effect of damage on thrust generated by propellers and to design a test rig to measure the thrust generated using a strain gauge. ANSYS is used to analyse the thrust and the airflow surrounding the propellers can be simulated after the results are generated. Learning how to use ANSYS takes up a lot of time and there are series of trials and errors when damaging the propellers. However, it is worthwhile since it helps in understanding the concepts of the analysis.